المــــجلس الدســــتوري الجزائري و المــــنازعة اإلنـــتخابية - سعاد صيد; سهيلة دحامنية (My University, 2017)
Summary: It is evident from our briefing on the various aspects between the Constitutional Council and the electoral dispute. and that by subjecting the latter to multiple types of censorship, from the supervision of legally specialized bodies to administrative oversight, Judicial oversight, that electoral disputes constitute a guarantee of democracy. The characterization of the Constitutional Council by the electoral judge as a supervisory body since the 1989 Constitution has cleared the preparatory course for the ballot of irregularities that may be distorted, interspersed or synchronized with a decision and chapter bearing therein either the abrogation, amendment or confirmation of the constitutional process. It is a meaningful pursuit of political stability in the State, framed by true democracy, especially transparency and integrity. .......................... ملـخـص: يتضح جليا من خلال إحاطتنا بمختلف الجوانب القائمة بين المجلس الدستوري و المنازعة الإنتخابية ، أنه ومن خلال إخضاع هذه الأخيرة لأنواع متعددة من الرقابة ، التي تتراوح بين رقابة هيئات متخصصة قانونا ، رقابة إدارية ، و رقابة قضائية ، أن المنازعات الإنتخابية تشكل ضمانا للديمقراطية .إن إضفاء وصف قاضي الإنتخابات على المجلس الدستوري كهيئة رقابية منذ دستور 1989 أدى إلى تطهير المسار التحضيري للإقتراع من المخالفات التي قد تشوبــه أو التي قد تتخلله أو تزامنه وصولا إلى بـت و فصل يحمل في طياته إما إلغاءا أو تعديلا أو تأكيدا لما تضمنته العملية الإنتخابية في مراحلها سالفة الذكر .لعل هذا التأكيد الحثيث الذي تضمنته نصوص الدستور و القانون العضوي للإنتخابــات و النظام المحدد لقواعد عمل المجلس الدستوري ، إنما هو سعي هادف لتحصيل إستقرار سياسي في الدولة تؤطره معالم الديمقراطية الحقة، لاسيما الشفافية و النزاهة. ........................... Résumè : A travers la discussion des différents aspects existants entre le Conseil constitutionnel et le contentieux électoral, ce dernier constitue l’une des garanties de la démocratie, étant donné que le processus électoral est soumis à plusieurs types de contrôle, administratif ou judiciaire, exercés par les instances habilitées. La qualité du Conseil constitutionnel en tant qu’instance à caractère judiciaire, depuis la Constitution de 1989, a conduit à déblayer le processus pré-électoral des irrégularités qui peuvent l’entacher et à annuler, modifier ou confirmer les résultats de l’opération électorale. Les textes constitutionnels, la loi organique relative au régime électoral ainsi que les règles de fonctionnement du Conseil Constitutionnel ont affirmé ledit rôle du Conseil dans le dessein de réaliser la stabilité politique, encadré par des repères d’une vraie démocratie, notamment la transparence et l'intégrité.